Diffusion process with evolution and its parameter estimation - Koroliuk, V.S.; Koroliouk, D.; Dovgyi S.О. (Кибернетика и системный анализ, 2020)
A discrete Markov process in an asymptotic diffusion environment with a uniformly ergodic embedded Markov chain can be approximated by an Ornstein–Uhlenbeck process with evolution. The drift parameter estimation is obtained using the stationarity of the Gaussian limit process.